Impact of ethnicity upon cardiovascular adaptation in competitive athletes: relevance to preparticipation screening - Papadakis, M.; Wilson, M. G.; Ghani, S.; Kervio, G.; Carre, F.; Sharma, S. (British Journal of Sports Medicine, 2012)
Regular participation in intensive physical exercise is associated with several structural and electrophysiological cardiac adaptations that enhance diastolic filling and facilitate a sustained increase in the cardiac output that is fundamental to athletic excellence. Such cardiac adaptations are collectively referred to as the `Athlete's Heart` and are frequently reflected on the 12-lead ECG and imaging studies. Thorough knowledge relating to exercise-associated cardiovascular adaptation is imperative for the purposes of differentiating physiological adaptation from cardiac pathology, since an erroneous diagnosis of cardiac disease has potentially serious consequences for the athlete's physical, psychological, social and financial well-being. The majority of studies investigating the cardiovascular adaptation to exercise are based on cohorts of Caucasian athletes. However, there is mounting evidence that ethnicity is an important determinant of the objective manifestations of cardiovascular adaptation to exercise. The most pronounced paradigm of ethnically distinct cardiovascular adaptation to exercise stems from athletes of African/Afro-Caribbean descent, who exhibit a significantly higher prevalence of repolarisation anomalies and left ventricular hypertrophy, compared to Caucasian athletes; the differentiation between athlete's heart and hypertrophic cardiomyopathy is particularly challenging in this ethnic group. The extrapolation of ECG and echocardiographic criteria used to diagnose potentially serious cardiac disorders in Caucasian athletes to the African/Afro-Caribbean athlete population would result in an unacceptable number of unnecessary investigations and increased risk of false disqualification from competitive sport. Accurate interpretation of the athlete's ECG and echocardiogram is crucial, particularly when one considers the continuous expansion of preparticipation screening programmes. This review attempts to highlight ethnically determined differences in cardiovascular adaptation to exercise and provides a practical guide for the interpretation of baseline investigations in athletes of diverse ethnic backgrounds.